2021
DOI: 10.2478/cttr-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of HPHC Reduction in THS 2.2 Aerosol Relative to 3R4F Reference Cigarette Smoke under Extreme Climatic Conditions

Abstract: Summary In order to assess robustness for the reduction of harmful and potentially harmful constituent (HPHC) levels generated by the Tobacco Heating System 2.2 (THS 2.2), a heated tobacco product, we compared the aerosol of this product with mainstream smoke from the 3R4F reference cigarette under different conditions of temperature and humidity. The desired climatic conditions were achieved by using an air-conditioning system coupled with the smoking-machine housing. Two extreme climatic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Therefore, reduction of the causative substances of ROS may be important. The causative substances of ROS include phenolic compounds, aromatic hydrocarbons, and metals (Caliri et al, 2021), which are present in HTP aerosol at low levels (Hashizume et al, 2023; Hirn et al, 2020; Poget et al, 2021). Additionally, our preliminary experiment showed that deterioration of ROS by antioxidant treatment (i.e., N ‐acetyl‐cysteine) effectively reduced EGFR activation by CS (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reduction of the causative substances of ROS may be important. The causative substances of ROS include phenolic compounds, aromatic hydrocarbons, and metals (Caliri et al, 2021), which are present in HTP aerosol at low levels (Hashizume et al, 2023; Hirn et al, 2020; Poget et al, 2021). Additionally, our preliminary experiment showed that deterioration of ROS by antioxidant treatment (i.e., N ‐acetyl‐cysteine) effectively reduced EGFR activation by CS (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Food and Drug Administration (U.S. FDA, 2012) has proposed guidance for assessing the harm reduction potential of a “modified risk tobacco product” (MRTP) based on the possibility that decreased toxicant exposure may lead to health benefits. One of the expected MRTPs is heated tobacco products (HTPs), which generate vapor by heating but not combusting tobacco leaves; thus, the aerosol contains lower levels of harmful constituents than CS (Hirn et al, 2020; Poget et al, 2021). Several previous studies showed that the aerosol of HTP elicited less biological effects in in vitro and in vivo studies, as well as clinical testing (Ito et al, 2019; Phillips et al, 2016; Thorne et al, 2020; Yuki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is supported by the majority of newly identified studies and reviews. Quantified levels of the HPHCs investigated were either substantially lower from HTPs than from cigarettes [34][35][36][37][38][39][40] or undetectable or unquantifiable for HTPs [41]. The observed reduction in HPHC yields for HTPs when compared to cigarettes remains even when experimental machine smoking of the products is conducted under a range of extreme conditions of temperature and humidity [36].…”
Section: Harmful and Potentially Harmful Constituents (Hphcs)mentioning
confidence: 99%
“…Quantified levels of the HPHCs investigated were either substantially lower from HTPs than from cigarettes [ 34 - 40 ] or undetectable or unquantifiable for HTPs [ 41 ]. The observed reduction in HPHC yields for HTPs when compared to cigarettes remains even when experimental machine smoking of the products is conducted under a range of extreme conditions of temperature and humidity [ 36 ]. A small number of additional identified studies or reviews reported levels of chemical constituents to be higher with HTPs than with cigarettes for some, but not all, of the HTPs investigated [ 39 , 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…The relevance of this product category lies in its potential as a harm reduction strategy, as HTPs have been shown to release lower levels of harmful and potentially harmful constituents (HPHCs) than cigarettes. For one of the marketleading HTPs, the Tobacco Heating System 2.2 (THS 2.2) developed by Philip Morris International (PMI) and marketed under the brand name IQOS™ [1], analytical studies have substantiated its potential for harm reduction by demonstrating that it releases on average > 90% lower levels of HPHCs versus a reference cigarette, even when using extreme puffing regimens and climatic conditions [2,3].…”
Section: Introductionmentioning
confidence: 99%